2011
DOI: 10.3133/sir20115127
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the hydrologic recovery of wetlands in the Northern Tampa Bay area, Florida

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS. For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit http://store.usgs.gov Any use of trade, product, or firm names is for descriptive purposes only and does not imply endorsement by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…data, 2009). The small size of this wetland makes it particularly responsive to the effects of below-average rainfall because the smaller storage capacity allows it to dry out more quickly (Metz, 2011). Few alterations have occurred at this wetland since monitoring began other than controlled burns of adjacent saw palmetto (Michael Hancock, Southwest Florida Water Management District, unpub.…”
Section: W-56mentioning
confidence: 99%
See 4 more Smart Citations
“…data, 2009). The small size of this wetland makes it particularly responsive to the effects of below-average rainfall because the smaller storage capacity allows it to dry out more quickly (Metz, 2011). Few alterations have occurred at this wetland since monitoring began other than controlled burns of adjacent saw palmetto (Michael Hancock, Southwest Florida Water Management District, unpub.…”
Section: W-56mentioning
confidence: 99%
“…3) by about 3 ft during the post-reduction period, which likely decreased induced leakage from the overlying surficial aquifer and from the wetland. Metz (2011) reported that an increase in the potentiometric surface of the Upper Florida aquifer below wetlands was the primary factor affecting hydrologic recovery of wetlands in well fields.…”
Section: Wetland Water Levelsmentioning
confidence: 99%
See 3 more Smart Citations